Postaxial hypoplasia of the lower extremity (fibular hemimelia) presenting in a young adult male - Özdemir, Meltem (Radiol Case Rep, 2019)
Postaxial hypoplasia of the lower extremity, formerly termed as fibular hemimelia, is characterized by lower limb length discrepancy and a broad spectrum of anomalies involving the ipsilateral limb. It is a rare skeletal abnormality with an incidence of 5.7-20 cases per 1 million births. Herein, we present a young man with postaxial hypoplasia of the lower extremity who admitted to the hospital for a reason other than musculoskeletal complaints. While his limb length discrepancy was rather mild, the accompanying tarsal coalition was of an extensive form involving talus, calcaneus, navicular, and cuboid. Such extensive fusions of the hindfoot are very rare, and they are commonly associated with congenital syndromes such as postaxial hypoplasia of the lower extremity and Alpert syndrome. Therefore, further investigation for accompanying abnormalities is needed in cases with extensive fusions of the hindfoot.